Participação política e gestão urbana sob o Estatuto da Cidade1 - Goulart, Jefferson Oliveira [UNESP]; Terci, Eliana Tadeu; Otero, Estevam Vanale (FapUNIFESP (SciELO), 2015)
The hegemonic version of democracy is based on Schumpeter's approach, a legacy of liberal pluralism that reduces the formation of legitimate majorities through representation. Nevertheless, the democratization of authoritarian countries has provided innovative experiences of civil society in new participatory formats. At the institutional level, the Statute of the City regulated the chapter of the Urban Policy of the Federal Constitution of 1988. It advocates participatory formats of public policies in urban management through public participation and representative associations. The construction of this agenda is the result of institutional imposition and it reflects the government decisions and civil society demands. This paper analyzes the participation, its ability to share decisions, and to what extent these participatory formats depend on governments for the implementation of new paradigms of urban management. The approach combines theoretical and empirical analysis of development processes of Master Plans normatively guided by the City Statute. The empirical basis is formed by three medium-sized cities in Sao Paulo state: Piracicaba, Bauru and Rio Claro.
Political participation and urban management under the Statute of the City
Keywords: Participation; Statute of the City; Urban management